If 6x - 2 = 4x + 12, then x= 3.

Skip to content# If 6x – 2 = 4x + 12, then x= 3.

### Related Posts

##
This Post Has 4 Comments

### Leave a Reply Cancel reply

Home
Mathematics
If 6x – 2 = 4x + 12, then x= 3.

If 6x - 2 = 4x + 12, then x= 3.

12cm

the answer is d

f(x) = - 2/3x + 5; f(5/2)

substitute 5/2 in for x:

f(5/2) = -2/3(5/2) + 5

simplify the right side:

f(5/2) = -5/3 + 5

f(5/2) = 10/3

answer:

f(5/2) = 10/3

i hope this you!

the correct answer is b. negative exponential growth.

step-by-step explanation:

you can tell it's an exponential function because it decreases rapidly then levels out and never touches the x-axis.

it is negative because the y-axis decreases as the x-axis increases.

therefore it is a negative exponential growth graph.

hope i !

[tex]Categorize the graph as linear increasing, linear decreasing, exponential growth, or negative expone[/tex]

4a. is 3 miles every hour

4b. is 1/3 of an hour per mile

step-by-step explanation:

[tex]Middle school. ratios.rita walks. for me[/tex]